Phytochemical Study On Sesbania Grandiflora Roots And Synthesis Of Selected Flavonoid Precursors (Chalcones Derivatives) - Noviany, Noviany (2014)
Sesbania grandiflora, a small tree up to 15 m tall, is a traditional medicinal plant collected from South Lampung, Indonesia. Some new and known compounds were isolated from the roots of this plant. They were identified as one terpenoid, betulinic acid (81), ten flavonoids, malindonesianin A-C (82, 86, 88), xenognosin B (83), liquiritigenin (84), 7,2’,4’-trihydroxyisoflavone (85), demethylvestitol (87), vestitol (89), medicarpin (90) and sativan (91), together with one biaryl compound, l,l’-binaphthalene-2,2’-diol (92). Among them, three compounds (82, 86, 88) were established as novel isoflavonoid dimers, while one compound (92) was found as new biaryl natural product. Chalcone is an important biosynthetic precursor, due to the diverse pharmacological activities. The aim of this current study was to synthesize 28 new chalcone derivatives compounds by incorporating p-alkoxyacetophenones with substituted benzaldehydes. Four new series of chalcone derivatives have been synthesized using the alkylation and the base catalysed Claisen-Schmidt condensation. All the synthesized compounds were fully characterized by IR, 1D NMR (1H and 13C NMR) and 2D NMR (COSY, HMQC, HMBC) as well as mass spectrometry analysis.